Moral Spiritual Education Through Quiet Book Media: Instilling Love for God's Creation in Preschool Children - Rahayu, Dika Putri; Himmatussa’idah, Nur; MR, Moh Irsyad Fahmi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research develops a quiet book media for preschool children. Character building in preschool children is an important foundation in forming personalities with noble character, caring for others, and having spiritual values. One of the main values is love for God's creatures, which is a holistic part of character building and needs to be stimulated through contextual learning. The age period of 3-4 years is a golden period where children are very receptive to the internalization of these values. Therefore, learning media that is interesting, interactive, and appropriate for children's development is needed. This research aims to develop Quiet Book media as an educational tool for instilling love for God's creation in preschool children. The research uses a Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects are playgroup children aged 3-4 years. Data collection techniques include observation and documentation. Validation was conducted by material experts and media experts, as well as practicality testing by teachers. Data analysis includes validity testing (V Aiken), reliability (Cronbach's Alpha), and effectiveness using n-gain test. The research results show that the Quiet Book media: 1) was developed according to media development needs, 2) was declared sufficiently valid by material experts (64.28%) and very valid by media experts (90.62%), 3) was assessed as very practical by teachers (88.46%), and 4) was sufficiently effective from small group (59.0%) and large group (57.6%) test results. Thus, the Quiet Book is suitable for use as a learning medium for the value of love for God's creation in early childhood.